Strive to Win or Not to Lose? Age-Related Differences in Framing Effects on Effort-Based Decision-Making. (20th October 2019) - Byrne, Kaileigh A; Ghaiumy Anaraky, Reza
Abstract: Objectives: This study sought to assess how framing effects modulate age-related differences in effort-based decision-making. Consistent with the selection, optimization, and compensation (SOC) model's loss prevention account of aging, we predicted that older adults would be more willing to select high-effort options in loss contexts than gain contexts. Method: Older and younger adults completed the effort expenditure for rewards task (EEfRT) in either a gain or loss context. The EEfRT is an effort-based decision-making paradigm in which participants choose between a low-effort, "easy" option and a high-effort, "hard" option for several trials. The probability and value of an outcome varies on a trial-by-trial basis. Results: The results supported our prediction and the SOC model. Older adults chose more high-effort, difficult options in loss frames than gain frames. Older adults also chose more low-effort, easy options than younger adults in gain contexts, but did not differ from younger adults in loss contexts. Discussion: These findings demonstrate that framing effects impact older adults' effort-based decisions. Older adults appear willing to incur a greater "cost" in the form of effort to prevent a loss than to attain a reward.